Crushing Hope: Short Term Responses to Tragedy Vary by Hopefulness - Jason M. Fletcher (Institute of Labor Economics (IZA), 2018)
This research note explores the consequences of dispositional optimism and hopefulness when the environment changes. Much literature has documented the importance of a positive outlook in pursuing investments in health and education that pay off in the future. A question that has received less attention is whether a positive outlook creates resilience in the face of setbacks or whether a positive outlook may be a disadvantage in extreme circumstances, especially when there is a large mismatch between expectations and reality. This paper uses the coincidental interview schedule of the Add Health data (N=15,024) around the terrorist attack of September 11, 2001 to examine interactions with this environmental shock and previously elicited measures of hopefulness. The results suggest that increases in depressive symptoms following the attack are concentrated among those young adults who initially expressed the most hopefulness in the future as teenagers.
Keywords: D91; I12; 330; evolutionary psychology; hopefulness; mismatch; depressive symptoms; trauma